Legal Protection For Notaries By The Notary Honorary Council as A Witness in The Case Of Identity Forgery By The Parties Making The Deed - Khairani; Argi Putra Finalo; Trie Rahmi Gettari (Master of Law Program, Ekasakti University, 2024)
Notary is a legal profession whose rights and obligations have been regulated in such a way in Law Number 30 of 2004 concerning the Notary Position (hereinafter referred to as UUJN). Where in Article 1 of the UUJN states